Carotid siphon morphology: Is it associated with posterior communicating aneurysms?. Issue 4 (August 2016) - Labeyrie, Paul-Emile; Gory, Benjamin; Huguet, Nazyad; Grenier, Charlotte; Ditac, Geoffroy; Sadeh-Gonik, Udi; Riva, Roberto; Turjman, Francis
Background and purpose: Posterior communicating artery (PComA) aneurysm seems to behave uniquely compared with other intracranial aneurysms at different locations. The association between the morphology of the carotid siphon and PComA aneurysms is not well known. This study aimed to investigate whether the anatomical characteristics of the carotid siphon are associated with the formation and rupture of PComA aneurysms. Methods: One hundred and thirty-two patients were retrospectively reviewed in a monocentric case–control study. Sixty-seven consecutive patients with PComA aneurysms were included in the case group, and 65 patients with anterior circulation aneurysm situated in other intracranial locations were included in the control group, matched by age and sex. Morphological characteristics of the carotid siphon were analyzed using angiography images. A univariate analysis was used to investigate the association between the morphological characteristics and the formation of PComA aneurysms. Furthermore, a subgroup analysis within the case group compared ruptured and non-ruptured PComA aneurysms. Results: Patients with PComA aneurysm had a significantly (1.31 ± 0.70 vs. 0.82 ± 0.46; P < 0.001) larger PComA. No association was observed between the morphological characteristics of the carotid siphon and the presence of a PComA aneurysm. Likewise, subgroup analysis showed no significant association between morphological characteristics of the carotid siphon and aneurysm rupture. Conclusions: This case–control study shows that the carotid siphon morphology seems not to be related to PComA aneurysm formation or rupture.